2013
DOI: 10.1177/0022042613511439
|View full text |Cite
|
Sign up to set email alerts
|

The Connections Between Substance Dependence, Offense Type, and Offense Severity

Abstract: The link between drug use and crime has been broadly described, but little detail is known about the contributions of alcohol and drug dependence to different types of offending. Data were drawn from the 2010 Arrestee Drug Abuse Monitoring II (ADAM II) program to examine the relationships between dependence, offense type, and severity among recent male arrestees ( N = 3,006). A substantial proportion (ranging from 15% to 39%) of arrestees across all offense types and severity levels endorsed drug-dependent ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 38 publications
2
24
1
Order By: Relevance
“…It is generally acknowledged that substance use and offending behavior are closely intertwined (Kopak et al 2014;Vaughn et al 2016). An estimated 50 to 66% of offenders meet DSM-IV criteria (American Psychiatric Association 2000) for substance abuse or dependence, whereas only 9% of the general population meet these criteria (Mumola and Karberg 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally acknowledged that substance use and offending behavior are closely intertwined (Kopak et al 2014;Vaughn et al 2016). An estimated 50 to 66% of offenders meet DSM-IV criteria (American Psychiatric Association 2000) for substance abuse or dependence, whereas only 9% of the general population meet these criteria (Mumola and Karberg 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The association between substance use and offending behavior can be explained by several reasons including that substance use may exacerbate psychological symptoms (Swanson et al 2008), thereby increasing the likelihood of offending behavior (Giancola 2004). Furthermore, offenders were arrested for drug trafficking and/or committed their offense to support their substance use (Kopak et al 2014). As a result, addiction treatment centers and criminal justice systems often deal with the same individuals and higher percentages of substance abuse and dependency are found in forensic samples (Chandler et al 2009;Lindsay et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Among those whose offense type was nonviolent, 54% were nondependent, 11% were alcohol dependent, 22% were drug dependent, and 14% were polysubstance dependent. Among those whose offense type was substance-related, 46% were nondependent, 10% were alcohol dependent, 30% were drug dependent, and 14% were polysubstance dependent (Kopak, Vartanian, Hoffmann, & Hunt, 2014). 4.…”
mentioning
confidence: 99%
“…Recent research has highlighted this relationship with the finding that arrestees who endorsed indicators of alcohol use disorders were most likely to be charged with lower level (i.e. misdemeanor) violent offenses, such as disorderly conduct or assault, while those who met criteria indicative of drug use disorders were significantly more likely than those that did not present these symptoms to be charged with felony-level drug offenses (Kopak et al, 2014b;Sevigny and Coontz, 2008). This means that arrestees with alcohol use disorders were likely to be involved in crimes which are addressed with much more lenient sanctions, while those with drug use disorders are most likely to be charged with felony offenses that resulted in lengthier prison sentences.…”
Section: Introductionmentioning
confidence: 99%
“…drug possession or possession of drug paraphernalia) or alcohol-related (e.g. disorderly conduct or assault) and research has shown that many arrestees who experience substance use disorders are charged with these types of offenses (Kopak and Hoffmann, 2014;Kopak et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%